Cultural Syncretism and Religious Authority: Early Ramadan Determination Practices in Maluku - Kilwakit, Marifat; Arif Zamhari (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2025)
Identifying the commencement of Ramadan in Indonesia encompasses religious and socio-cultural dimensions, illustrating the intricate interplay between Islamic doctrine and local traditions. This study adopts a qualitative methodology and field research techniques to explore harmonizing these elements in establishing the onset of Ramadan in Maluku. Findings indicate that the Maluku community perceives local customs as an essential aspect that should be integrated into all religious rituals and practices, including the early declaration of Ramadan. The method employed annually to determine Ramadan's beginning is regarded as a legitimate cultural heritage with authenticity and alignment with Islamic principles. In Maluku, religious symbols and traditional practices in observing the new moon via natural indicators are frequently utilized concurrently to ascertain the start of Ramadan. This interplay fosters a symbolic dynamic that merges scientific methodologies with traditional practices, influenced by the roles of national religious bodies and local indigenous communities.